(untitled) (Shodhmala शोधमाला, 2026)
This article looks at the real lives of the Magar community, an indigenous tribe that lives in squatter communities in Kathmandu, with an emphasis on Sinamangal. It looks at how cultural identity, economic hardship, and systematic exclusion all come together to affect daily living in urban informal settings. The study underscores the ongoing difficulties encountered by Magar families, such as restricted access to housing, education, healthcare, and employment prospects, as well as experiences of marginalization within urban governance frameworks. The research utilizes field observations and comprehensive interviews to record patterns of survival, resilience, and collective support that maintain community cohesion in the face of difficult conditions. It also talks about how cultural practices and identity negotiations are developing in cities. The findings show how being an indigenous person affects your access to rights, resources, and social recognition in the city. This article advocates for immediate policy measures to combat urban poverty while promoting inclusive development frameworks that respect indigenous rights, dignity, and wellbeing. The study ultimately contributes to broader discourses on indigeneity, urbanization, and social justice in Nepal.